シラセ サイヒョウ コウコウ データ ガ シメス ナンキョク リュツォ・ホルムワン テイチャクヒョウ ノ ネンネン ヘンカ - 牛尾, 収輝; ウシオ, シュウキ; 宇都, 正太郎; ウト, ショウタロウ; 泉山, 耕; イズミヤマ, コウ; 下田, 春人; シモダ, ハルヒト; 鮎川, 勝; アユカワ, マサル; Ushio, Shuki; Uto, Shotaro; et al. (2004)
P(論文) 南極リュツォ・ホルム湾において毎年ほぼ同時期,同海域を航海する砕氷船「しらせ」は,海氷モニタリング・プラットフォームに適している.同湾の海氷状況の年々変化を推測するために,1983年から2002年までの間の「しらせ」砕氷航行データを解析した.主にラミング砕氷と氷厚や積雪深との関係を調べ,ラミング一回当たりの進出距離を砕氷航行の難易度の指標とすることにより,定着氷域の変化の特徴を抽出した.ラミング時の進出距離が短い1990年代前・中期は,航海が困難で厳しい氷状を反映し,氷厚や積雪深が大きい.一方,1990年代終わりから2002年までの間は,進出距離が長い傾向にあり,湾内定着氷の崩壊・流出の頻発期とも符合していることがわかった. Characteristics of sea-ice conditions in Lutzow-Holmbukta, Antarctica, have been investigated using the ice navigation log from the icebreaker Shirase, which has made a voyage almost at the same season and in the same sailing route every year since 1983. The vessel is considered as a suitable monitoring platform for sea ice. Not only basic information such as ice thickness and snow depth, but also ramming icebreaking data have been analyzed. In particular, the penetrating distances by ramming reflect difficulty in ice navigation and show distinctly interannual variations from 1983 to 2002. The periods with longer distances are consistent with those when breakup of landfast ice occurred frequently in the bay. The penetrating distances have shown a tendency to increase since the end of the 1990s, when ice breakup has been pronounced. departmental bulletin paper